2020
DOI: 10.3390/ijerph17010356
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Periodontal Treatment and Decreased Pneumonia: A Nationwide Population-Based Cohort Study

Abstract: Pneumonia is a common respiratory infectious disease that involves the inflammation of the pulmonary parenchyma. Periodontal disease is widespread and correlated with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
2
26
0
3
Order By: Relevance
“…Some epidemiologic studies found no clear relationship between periodontal hygiene and acute respiratory disease 31,32 . However, some studies have reported the association between periodontal disease and pneumonia [33][34][35] , and Yang et al reported that patients with periodontal treatment exhibited a decreased risk of pneumonia 36 . In this study, NHIS-HealS data did not include the severity and treatment of periodontal disease; therefore, the two factors could potentially be found to be unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiologic studies found no clear relationship between periodontal hygiene and acute respiratory disease 31,32 . However, some studies have reported the association between periodontal disease and pneumonia [33][34][35] , and Yang et al reported that patients with periodontal treatment exhibited a decreased risk of pneumonia 36 . In this study, NHIS-HealS data did not include the severity and treatment of periodontal disease; therefore, the two factors could potentially be found to be unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…The LHID2010 incorporates 1 million patients’ insurance claims data from the total of 23 million Taiwan NHI beneficiaries in the year 2010. There are no demographic characteristic differences between the LHID2010 and the original NHIRD [ 16 , 17 ]. The LHID2010 contains the most updated claims data of sampled individuals from 1997.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with diabetes had a 78% increased risk of developing pneumonia compared to the control group. 12 These findings indicate that the multimorbid patient with diabetes and periodontitis as a comorbidity has a frighteningly high risk of pneumonia even without SARS-CoV-2 infection.…”
mentioning
confidence: 80%